Improving Elementary School Students' Understanding Through Islamic Education Teaching Materials Based on the Local Wisdom of the Cigugur Community - Novianti Muspiroh; Gulden - Uyanik (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2024)
Elementary school students' understanding of Islamic Religious Education is often hindered by the lack of relevance between teaching materials and everyday life. This research aims to develop teaching materials based on the local wisdom of the Cigugur community as an innovative approach to enhance students' understanding of Islamic Religious Education content. The research method used is research and development (R&D) with the Borg and Gall model. The study involved 80 students as the experimental group and 50 students as the control group from several elementary schools in Cigugur District. Data collection techniques included questionnaires, comprehension tests, and observations of the learning process, while data analysis was conducted using t-tests and N-gain calculations. The results of the study indicate that teaching materials based on Cigugur's local wisdom effectively improve students' understanding compared to conventional methods. The integration of local cultural values into Islamic Religious Education makes the material more contextual, relevant, and engaging, while fostering students' critical thinking and problem-solving skills. Additionally, this approach contributes to the preservation of local culture, builds students' appreciation for regional traditions, and encourages active engagement in the learning process. This study provides an innovative model for developing teaching materials based on local wisdom in various regions as a solution to improving the quality of education in Indonesia.Keywords: Islamic Religious Education, teaching materials, local wisdom, students' understanding